Preparation method of NiO-based 2-chloroethyl ethyl sulfide gas sensor

Through the preparation method of NiO-based 2-chloroethyl ethyl sulfide gas sensor, the existing sensor has solved the problems of high working temperature, low response value and long recovery time, and achieved the gas detection effect of low temperature, high sensitivity and rapid recovery.

CN119915870AActive Publication Date: 2025-05-02HEILONGJIANG UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510119064.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-05-02
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The existing 2-CEES gas sensors have problems such as high operating temperature, low response value and long recovery time.

Method used

Using the preparation method of NiO-based 2-chloroethyl ethyl sulfide gas sensor, ceramic tubes with NiO/metal oxide composite material grown on the surface were prepared by the composite of nickel sulfate hexahydrate and metal salt, impregnation and heating, calcination and aging.

Benefits of technology

The operating temperature of the gas sensor is reduced to 150℃, the response value is improved, the recovery time is shortened, the selectivity is good, and the detection limit is extremely low (0.07ppm), which can efficiently detect 2-CEES gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119915870A_ABST
    Figure CN119915870A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a NiO-based 2-chloroethyl ethyl sulfide gas sensor, and belongs to the technical field of gas sensors. The problems that an existing 2-CEES gas sensor is high in working temperature, low in response value and long in recovery time are solved. The method comprises the following steps: 1, compounding nickel sulfate hexahydrate and metal salt; 2, adding ammonia water; 3, dipping and heating; 4, calcining; and 5, aging. The preparation method disclosed by the invention is used for preparing the NiO-based 2-chloroethyl ethyl sulfide gas sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gas sensors. Background Art

[0002] Dichlorodiethyl sulfide is a foaming agent that is extremely harmful to the environment and humans. Excessive inhalation of this gas by the human body can cause serious organ damage, so dichlorodiethyl sulfide must be effectively detected. Due to the high toxicity of the gas, it is very dangerous to conduct experiments in the laboratory. Therefore, in the experiment, simulated gases with similar physical and chemical properties are generally used, and this type of simulated gas is less toxic. The chemical gas 2-chloroethyl ethyl sulfide (2-CEES) gas is often used as a simulated gas for dichlorodiethyl sulfide in the laboratory.

[0003] At present, there are many 2-CEES gas detection methods, such as ion mobility spectroscopy, gas chromatography-mass spectrometry and Raman spectroscopy, but these detection methods are expensive and time-consuming, and are not suitable for practical applications. In contrast, metal oxide semiconductor gas sensors have been used to detect low-concentration gases due to their simplicity, low cost and high portability.

[0004] However, there is little research on 2-CEES sensors. Only one Chinese patent application document with publication number CN116642928A introduces a preparation method based on WO3 / Al2O3 / graphite composite material, in which WO3 and Al2O3 are fully mixed in a mortar, and calcined at high temperature to collect solid products, and then mixed with graphite solution, and WO3 / Al2O3 / graphite solution is obtained by continuous stirring, and the gas-sensitive material is obtained by drying. When preparing the sensor, the material is mixed with water and evenly coated on a ceramic tube to respond to 2-CEES gas, but it has the problem of too low response value, which is only about 69%, and the operating temperature is also high; some metal oxide gas sensors for detecting 2-CEES gas are also reported in the literature, such as Li et al. (Baosheng Li, Xue Ma, Yuying Xin, Zoltán Major, Xianfa Zhang, Tingting Wang, Lihua Huo, Xiaoli Cheng, Yingming Xu, In situ construction of hierarchical Fe2O3 nanotube arrays for real-time detection and degradation of 2-CEES gas, Sensors andActuators B:Chemical,Volume 383,2023,133590) constructed a Fe2O3 material for detecting 2-CEES gas. The recovery time of the sensor was 190 seconds, indicating that its recovery was poor. For example, Yoo et al. (Ran Yoo1, Chihon Oh, Min-Jung Song, Sungmee Cho, and Wooyoung Lee.Journal of Nanoscience and Nanotechnology, Volume 18, Number 2, February 2018, pp. 1232-1236 (5)) created a ZnO material for detecting 2-CEES gas. However, its operating temperature was 500°C and the recovery time was 127 seconds, indicating that its operating temperature was too high and its recovery was poor.

[0005] It can be seen that the existing 2-CEES gas sensor has the problems of high operating temperature, low response value and long recovery time. Summary of the invention

[0006] The present invention aims to solve the problems of high operating temperature, low response value and long recovery time of the existing 2-CEES gas sensor, and further provides a method for preparing a NiO-based 2-chloroethyl ethyl sulfide gas sensor.

[0007] The preparation method of NiO-based 2-chloroethyl ethyl sulfide gas sensor is carried out according to the following steps:

[0008] 1. Composite of nickel sulfate hexahydrate and metal salts:

[0009] Dissolve nickel sulfate hexahydrate and metal salt in deionized water and stir magnetically to obtain a clear and transparent solution;

[0010] 2. Add ammonia:

[0011] Add ammonia water to the clear transparent solution and continue magnetic stirring to obtain a green solution;

[0012] 3. Immersion Heating:

[0013] The ceramic tube is immersed in the green solution and sealed, reacted for 4 hours to 24 hours at a temperature of 120°C to 200°C, then cooled to room temperature, the ceramic tube is taken out, washed and dried to obtain an immersed ceramic tube;

[0014] 4. Calcination:

[0015] The impregnated ceramic tube is calcined for 1 h to 4 h in an air atmosphere at a temperature of 400° C. to obtain a ceramic tube with a NiO / metal oxide composite material grown on the surface;

[0016] The metal oxide is iron oxide, copper oxide, cadmium oxide, zinc oxide, silver oxide, cobalt oxide or magnesium oxide;

[0017] 5. Aging:

[0018] A ceramic tube with a NiO / metal oxide composite material grown on the surface is welded to a base and then subjected to an aging treatment to obtain a NiO-based 2-chloroethyl ethyl sulfide gas sensor.

[0019] The beneficial effects of the present invention are:

[0020] (1) This synthesis method can be performed in situ on a ceramic tube substrate and has excellent development and application prospects.

[0021] (2) The synthesis method of this material is simple and low-cost. The solvent used is water, which is environmentally friendly and more suitable for large-scale production.

[0022] (3) The gas sensor has a low operating temperature (150°C), ultra-high sensitivity, low response value, fast response recovery capability, good selectivity, and extremely low detection limit (0.07ppm), and can detect 2-CEES gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is an XRD image of the NiO gas-sensitive material in the ceramic tube with NiO grown on the surface prepared in step 4 of Example 8;

[0024] Figure 2 This is a SEM image of the NiO gas-sensitive material in the ceramic tube with NiO grown on the surface prepared in step 4 of Example 8;

[0025] Figure 3 The gas-sensing performance test diagrams of the gas sensor prepared in Example 8, (a) the response diagram to 100 ppm 2-CEES gas at different working temperatures, (b) the selectivity to 2-CEES gas at 150°C, (c) the response and recovery time to 100 ppm 2-CEES gas at 150°C, (d) the response value to 0.1 ppm 2-CEES gas at 150°C;

[0026] Figure 4 The gas-sensing performance test diagrams of the gas sensor prepared in Example 8 at 150° C. are (ab) responses to 2-CEES gas in the concentration range of 0.07 ppm to 100 ppm, (cd) the relationship between the response value of 2-CEES gas and the gas concentration, (e) the response recovery process of 100 ppm 2-CEES gas for 5 consecutive times, and (f) the performance test of 100 ppm 2-CEES gas within 70 days;

[0027] Figure 5 XRD image and SEM image of NiO / Fe2O3 gas-sensitive material in the ceramic tube with NiO / Fe2O3 composite material grown on the surface prepared in step 4 of Example 1;

[0028] Figure 6 is the response recovery curve of the gas sensor prepared in Example 1 to 50 ppm of 2-CEES gas at 150°C;

[0029] Figure 7 XRD image and SEM image of the NiO / CuO gas-sensitive material in the ceramic tube with the NiO / CuO composite material grown on the surface prepared in step 4 of Example 2;

[0030] Figure 8 is the response recovery curve of the gas sensor prepared in Example 2 to 50 ppm of 2-CEES gas at 150°C;

[0031] Fig. 9 XRD image and SEM image of NiO / CdO gas-sensitive material in the ceramic tube with NiO / CdO composite material grown on the surface prepared in step 4 of Example 3;

[0032] Fig.10 is the response recovery curve of the gas sensor prepared in Example 3 to 50 ppm of 2-CEES gas at 150°C;

[0033] Fig.11 The XRD image and SEM image of the NiO / ZnO gas-sensitive material in the ceramic tube with the NiO / ZnO composite material grown on the surface prepared in step 4 of Example 4;

[0034] Fig.12 is the response recovery curve of the gas sensor prepared in Example 4 to 50 ppm of 2-CEES gas at 150°C;

[0035] Fig.13 XRD image and SEM image of the NiO / Ag2O gas-sensitive material in the ceramic tube with NiO / Ag2O composite material grown on the surface prepared in step 4 of Example 5;

[0036] Fig.14 is the response recovery curve of the gas sensor prepared in Example 5 to 50 ppm of 2-CEES gas at 150°C;

[0037] Fig.15 XRD image and SEM image of the NiO / Co3O4 gas-sensitive material in the ceramic tube with NiO / Co3O4 composite material grown on the surface prepared in step 4 of Example 6;

[0038] Fig.16 is the response recovery curve of the gas sensor prepared in Example 6 to 50 ppm of 2-CEES gas at 150°C;

[0039] Fig.17 XRD image and SEM image of the NiO / MgO gas-sensitive material in the ceramic tube with the NiO / MgO composite material grown on the surface prepared in step 4 of Example 7;

[0040] Fig.18 This is the response recovery curve of the gas sensor prepared in Example 7 to 50 ppm of 2-CEES gas at 150°C. DETAILED DESCRIPTION

[0041] Specific implementation method 1: The preparation method of the NiO-based 2-chloroethyl ethyl sulfide gas sensor in this implementation method is carried out according to the following steps:

[0042] 1. Composite of nickel sulfate hexahydrate and metal salts:

[0043] Dissolve nickel sulfate hexahydrate and metal salt in deionized water and stir magnetically to obtain a clear and transparent solution;

[0044] 2. Add ammonia:

[0045] Add ammonia water to the clear transparent solution and continue magnetic stirring to obtain a green solution;

[0046] 3. Immersion Heating:

[0047] The ceramic tube is immersed in the green solution and sealed, reacted for 4 hours to 24 hours at a temperature of 120°C to 200°C, then cooled to room temperature, the ceramic tube is taken out, washed and dried to obtain an immersed ceramic tube;

[0048] 4. Calcination:

[0049] The impregnated ceramic tube is calcined for 1 h to 4 h in an air atmosphere at a temperature of 400° C. to obtain a ceramic tube with a NiO / metal oxide composite material grown on the surface;

[0050] The metal oxide is iron oxide, copper oxide, cadmium oxide, zinc oxide, silver oxide, cobalt oxide or magnesium oxide;

[0051] 5. Aging:

[0052] A ceramic tube with a NiO / metal oxide composite material grown on the surface is welded to a base and then subjected to an aging treatment to obtain a NiO-based 2-chloroethyl ethyl sulfide gas sensor.

[0053] The beneficial effects of this embodiment are:

[0054] (1) This synthesis method can be performed in situ on a ceramic tube substrate and has excellent development and application prospects.

[0055] (2) The synthesis method of this material is simple and low-cost. The solvent used is water, which is environmentally friendly and more suitable for large-scale production.

[0056] (3) The gas sensor has a low operating temperature (150°C), ultra-high sensitivity, low response value, fast response recovery capability, good selectivity, and extremely low detection limit (0.07ppm), and can detect 2-CEES gas.

[0057] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the metal salt described in step 1 is ferric nitrate nonahydrate, copper acetate, cadmium acetate, zinc acetate, silver acetate, cobalt acetate or magnesium chloride. The rest is the same as specific embodiment 1.

[0058] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the molar ratio of nickel sulfate hexahydrate to metal salt in step 1 is 1:(0-0.2). Other aspects are the same as specific embodiment 1 or 2.

[0059] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the volume ratio of the molar number of nickel sulfate hexahydrate to deionized water in step 1 is 1 mmol: (5-20) mL. The rest is the same as specific embodiment 3.

[0060] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the magnetic stirring described in step 1 is specifically for 0.5h to 2h at a rotation speed of 50rpm to 3000rpm; the magnetic stirring described in step 2 is specifically for 0.5h to 2h at a rotation speed of 50rpm to 3000rpm. Others are the same as specific embodiments 1 to 4.

[0061] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that the volume ratio of the clear transparent solution to ammonia water in step 2 is 1:(0.03-0.1). Other aspects are the same as specific implementation methods 1 to 5.

[0062] Specific implementation method 7: This implementation method is different from specific implementation methods 1 to 6 in that the mass percentage of the ammonia water in step 2 is 5% to 20%. The rest is the same as specific implementation methods 1 to 6.

[0063] Specific implementation eight: This implementation differs from specific implementations one to seven in that the ceramic tube in step three is an Al2O3 ceramic tube. The rest is the same as specific implementations one to seven.

[0064] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 4, the temperature is raised to 400° C. to 700° C. at a heating rate of 1° C. / min to 5° C. / min in air atmosphere. The rest is the same as specific embodiments 1 to 8.

[0065] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the aging treatment described in step 5 is specifically performed at a temperature of 90° C. to 150° C. for 24 h to 72 h. The rest is the same as specific embodiments 1 to 9.

[0066] The following examples are used to verify the beneficial effects of the present invention:

[0067] Embodiment 1:

[0068] The preparation method of NiO-based 2-chloroethyl ethyl sulfide gas sensor is carried out according to the following steps:

[0069] 1. Composite of nickel sulfate hexahydrate and metal salts:

[0070] Dissolve nickel sulfate hexahydrate and metal salt in deionized water, stir magnetically for 0.5 h at a rotation speed of 500 rpm, and obtain a clear and transparent solution;

[0071] The molar ratio of nickel sulfate hexahydrate to metal salt is 1:0.05;

[0072] The volume ratio of the molar number of the nickel sulfate hexahydrate to the deionized water is 2.66mmol:30mL;

[0073] The metal salt is ferric nitrate nonahydrate;

[0074] 2. Add ammonia:

[0075] Ammonia water was added to the clear transparent solution, and magnetic stirring was continued for 1.5 h at a rotation speed of 500 rpm to obtain a green solution;

[0076] The volume ratio of the clear and transparent solution to the ammonia water is 1:0.033; the mass percentage of the ammonia water is 10%;

[0077] 3. Immersion Heating:

[0078] The ceramic tube is immersed in the green solution and sealed, reacted at a temperature of 180°C for 4 hours, then cooled to room temperature, the ceramic tube is taken out, washed and dried to obtain an immersed ceramic tube;

[0079] 4. Calcination:

[0080] In an air atmosphere, the temperature is raised to 500°C at a heating rate of 2°C / min, and the impregnated ceramic tube is calcined for 2 hours in an air atmosphere at a temperature of 500°C to obtain a ceramic tube with a NiO / Fe2O3 composite material grown on the surface;

[0081] 5. Aging:

[0082] A ceramic tube with a NiO / Fe2O3 composite material grown on the surface was welded to a base and then aged at 150°C for 24 hours to obtain a NiO-based 2-chloroethyl ethyl sulfide gas sensor.

[0083] The ceramic tube described in step three is an Al2O3 ceramic tube, and is cleaned three times with deionized water; there are two gold electrodes on the Al2O3 ceramic tube, the distance between the electrodes is about 2 mm, and each electrode is connected by a platinum wire.

[0084] Embodiment 2: This embodiment is different from Embodiment 1 in that the metal salt in step 1 is cupric acetate, and in step 4, a ceramic tube with a NiO / CuO composite material grown on the surface is prepared. The rest is the same as Embodiment 1.

[0085] Embodiment 3: This embodiment is different from Embodiment 1 in that the metal salt in step 1 is cadmium acetate, and step 4 prepares a ceramic tube with a NiO / CdO composite material grown on the surface. The rest is the same as Embodiment 1.

[0086] Embodiment 4: This embodiment is different from Embodiment 1 in that the metal salt in step 1 is zinc acetate, and step 4 prepares a ceramic tube with a NiO / ZnO composite material grown on the surface. Others are the same as Embodiment 1.

[0087] Embodiment 5: This embodiment is different from Embodiment 1 in that the metal salt in step 1 is silver acetate, and in step 4, a ceramic tube with a NiO / Ag2O composite material grown on the surface is prepared. The rest is the same as Embodiment 1.

[0088] Example 6: This example is different from Example 1 in that the metal salt in step 1 is cobalt acetate, and step 4 prepares a ceramic tube with NiO / Co3O4 composite material grown on the surface. Other steps are the same as Example 1.

[0089] Embodiment 7: This embodiment is different from Embodiment 1 in that the metal salt in step 1 is magnesium chloride, and in step 4, a ceramic tube with a NiO / MgO composite material grown on the surface is prepared. The rest is the same as Embodiment 1.

[0090] Embodiment 8: The difference between this comparative experiment and embodiment 1 is that: the use of metal salt is omitted in step 1; and a ceramic tube with NiO grown on the surface is prepared in step 4. The rest is the same as embodiment 1.

[0091] The gas sensor prepared in the embodiment was tested for its gas-sensing performance of 2-CEES gas:

[0092] The test platform is the JF02F sensor test system of Kunming Guiyan Jinfeng Technology Co., Ltd. The test process is as follows: the temperature and humidity of the test are 25±1℃ and 30±5%RH respectively. The gas-sensitive test process is divided into the following steps: First, use a vacuum pump to evacuate the 10000mL gas chamber to a vacuum, use a syringe to inject the gas to be tested, and then inject clean air into the gas chamber to balance the pressure inside and outside the bottle. When the voltage of the gas sensor in the air remains stable, place the gas sensor in the gas chamber. When the gas sensor comes into contact with 2-CEES gas, the resistance of the gas sensor will change. After timing for 100 seconds, take the sensor out of the gas chamber and recover in the air.

[0093] Figure 1 This is the XRD image of the NiO gas-sensitive material in the ceramic tube with NiO grown on the surface prepared in step 4 of Example 8; the XRD diagram shows that the characteristic diffraction peaks appearing at 37.3°, 43.3°, 62.9° and 75.4° correspond to the (111), (200), (220) and (311) crystal planes of NiO, respectively (JCPDS No.04-0835).

[0094] Figure 2 This is a SEM image of the NiO gas-sensitive material in the ceramic tube with NiO grown on the surface prepared in step 4 of Example 8. As shown in the figure, the strip-shaped NiO material grows closely on the surface of the ceramic tube.

[0095] Figure 3 The gas-sensing performance test diagrams of the gas sensor prepared in Example 8, (a) the response diagram to 100ppm 2-CEES gas at different operating temperatures, (b) the selectivity to 2-CEES gas at 150°C, (c) the response and recovery time to 100ppm 2-CEES gas at 150°C, (d) the response value to 0.1ppm 2-CEES gas at 150°C; at different operating temperatures, the response of the gas sensor prepared in Example 8 to 100ppm 2-CEES gas is shown in FIG. Figure 3 As shown in (a), Figure 3 As can be seen in (a), when the operating temperature is 150 °C, the sensor has the highest response value to 100 ppm of 2-CEES gas; the selectivity of the NiO sensor to 2-CEES gas, such as Figure 3 As shown in (b), Figure 3 As can be seen in (b), the response values ​​of the NiO sensor to 100ppm ethanol, acetone, toluene, n-pentanol, diethylamine, formaldehyde, and hydrazine hydrate at 150℃ are relatively low, while the response to 2-CEES at a concentration of 100ppm is relatively large, much higher than the response of other gases; therefore, in summary, the optimal operating temperature of the NiO sensor for detecting 2-CEES gas is 150℃. Figure 3 As shown in (c), the response and recovery time of the NiO sensor to 100ppm of 2-CEES gas at an operating temperature of 150℃ are 100 seconds and 98 seconds respectively, and the response value is 42.5. The response value of the NiO sensor to 0.1ppm of 2-CEES gas is 2.21, as shown in Figure 3 As shown in (d), this shows that the NiO sensor can detect extremely low concentrations of 2-CEES gas well. This is also beneficial to the practical application of NiO sensors, and can detect the leakage of 2-CEES gas as early as possible.

[0096] Figure 4The gas-sensing performance test diagrams of the gas sensor prepared in Example 8 at 150°C are as follows: (ab) response to 2-CEES gas in the concentration range of 0.07ppm to 100ppm, (cd) relationship between the response value of 2-CEES gas and gas concentration, (e) response recovery process of 100ppm 2-CEES gas for 5 consecutive times, (f) performance test of 100ppm 2-CEES gas within 70 days; response to 2-CEES gas in the concentration range of 0.07ppm to 100ppm, as shown in FIG. Figure 4 (ab) as shown, from Figure 4 As can be seen from (ab), as the 2-CEES gas concentration increases from 0.7ppm to 100ppm, the sensor's response value to 2-CEES gas also increases from 1.2 to 42.5. Figure 4 As shown in (cd), there is a linear relationship between the response value of the NiO sensor to 2-CEES gas and the gas concentration, indicating that the detection range of the NiO sensor to 2-CEES gas is between 0.07ppm and 100ppm. At the optimal working temperature of 150℃, the response recovery test of 100ppm 2-CEES gas was carried out for 5 consecutive times. The test results are shown in Figure 4 As shown in (e), it can be seen from the figure that the resistance of the sensor can be restored to the initial resistance state every time, which shows that the NiO sensor has good reproducibility for 2-CEES gas. Next, the gas sensing performance of the NiO sensor for 100ppm 2-CEES gas was tested every seven days within 70 days. Figure 4 As shown in (f), it can be seen from the figure that the response value of the sensor did not change much during the 70-day test period, which shows that the sensor has good long-term stability for 2-CEES gas.

[0097] Embodiment 8 First, NiO material is in-situ grown on a ceramic tube, which has the advantages of simple manufacturing method, green environmental protection, and low cost. The obtained NiO sensor for 2-CEES gas detection has the advantages of high sensitivity, extremely low detection limit, and low operating temperature, and can provide timely warning of 2-CEES gas leakage.

[0098] Figure 5 The XRD image and SEM image of the NiO / Fe2O3 gas-sensitive material in the ceramic tube with NiO / Fe2O3 composite material grown on the surface prepared in step 4 of Example 1; it can be seen from the figure that the prepared material is a composite material of NiO and Fe2O3, and the NiO / Fe2O3 composite material is tightly grown on the surface of the ceramic tube.

[0099] Figure 6This is the response recovery curve of the gas sensor prepared in Example 1 to 50 ppm of 2-CEES gas at 150°C; it can be seen from the figure that the NiO / Fe2O3 composite material sensor can detect 2-CEES gas.

[0100] The gas sensor prepared in Example 1 has the best gas-sensing performance at 150°C, with a response value of 48.5 (50ppm), response recovery time of 11s and 67s (50ppm), respectively, and has good selectivity, reproducibility (5 consecutive times), and long-term stability (70 days). The sensor has a good linear relationship between the concentration and response value of 0.7ppm to 50ppm 2-CEES gas. As the concentration of 2-CEES gas increases from 0.7ppm to 50ppm, the response value of the sensor to 2-CEES gas also increases from 2 to 48.5.

[0101] Figure 7 XRD image and SEM image of the NiO / CuO gas-sensitive material in the ceramic tube with NiO / CuO composite material grown on the surface prepared in step 4 of Example 2; it can be seen from the figure that the prepared material is a composite material of NiO and CuO, and the NiO / CuO composite material grows tightly on the surface of the ceramic tube.

[0102] Figure 8 This is the response recovery curve of the gas sensor prepared in Example 2 to 50 ppm of 2-CEES gas at 150°C; it can be seen from the figure that the NiO / CuO composite material sensor can detect 2-CEES gas.

[0103] The gas sensor prepared in Example 2 has the best gas-sensing performance (50ppm) at 150°C, a response value of 12.5 (50ppm), and response recovery times of 16s and 105s (50ppm), respectively, and has good selectivity, reproducibility (5 consecutive times), and long-term stability (70 days). The sensor has a good linear relationship between the concentration and response value of 2-CEES gas of 1ppm to 50ppm. As the concentration of 2-CEES gas increases from 1ppm to 50ppm, the response of the sensor to 2-CEES gas also increases from 1.2 to 12.5.

[0104] Fig. 9 The XRD image and SEM image of the NiO / CdO gas-sensitive material in the ceramic tube with NiO / CdO composite material grown on the surface prepared in step 4 of Example 3; as can be seen from the figure, the prepared material is a composite material of NiO and CdO, and the NiO / CdO composite material grows tightly on the surface of the ceramic tube.

[0105] Fig.10This is the response recovery curve of the gas sensor prepared in Example 3 to 50 ppm of 2-CEES gas at 150°C; it can be seen from the figure that the NiO / CdO composite material sensor can detect 2-CEES gas.

[0106] The gas sensor prepared in Example 3 has the best gas-sensing performance at 150°C, with a response value of 14.8 (50ppm), response recovery time of 56s and 300s (50ppm), respectively, and has good selectivity, reproducibility (5 consecutive times), and long-term stability (70 days). The sensor has a good linear relationship between the concentration and response value of 2-CEES gas from 0.9ppm to 50ppm. As the concentration of 2-CEES gas increases from 0.9ppm to 50ppm, the response of the sensor to 2-CEES gas also increases from 1.2 to 14.8.

[0107] Fig.11 These are the XRD image and SEM image of the NiO / ZnO gas-sensitive material in the ceramic tube with the NiO / ZnO composite material grown on the surface prepared in step 4 of Example 4; as can be seen from the figure, the prepared material is a composite material of NiO and ZnO, and the NiO / ZnO composite material grows tightly on the surface of the ceramic tube.

[0108] Fig.12 Response recovery curve of the gas sensor prepared in Example 4 to 50 ppm of 2-CEES gas at 150° C. It can be seen from the figure that the NiO / ZnO composite material sensor can detect 2-CEES gas.

[0109] The gas sensor prepared in Example 4 has the best gas-sensing performance at 150°C, with a response value of 3.8 (50ppm), response recovery time of 60s and 1300s (50ppm), respectively, and good selectivity, reproducibility (5 consecutive times), and long-term stability (70 days). The sensor has a good linear relationship between the concentration and response value of 5ppm to 50ppm of 2-CEES gas. As the concentration of 2-CEES gas increases from 5ppm to 50ppm, the response of the sensor to 2-CEES gas also increases from 1.2 to 3.8.

[0110] Fig.13 The XRD image and SEM image of the NiO / Ag2O gas-sensitive material in the ceramic tube with the NiO / Ag2O composite material grown on the surface prepared in step 4 of Example 5; it can be seen from the figure that the prepared material is a composite material of NiO and Ag2O, and the NiO / Ag2O composite material grows tightly on the surface of the ceramic tube.

[0111] Fig.14This is the response recovery curve of the gas sensor prepared in Example 5 to 50 ppm of 2-CEES gas at 150°C; it can be seen from the figure that the NiO / Ag2O composite material sensor can detect 2-CEES gas.

[0112] The gas sensor prepared in Example 5 has the best gas-sensing performance at 150°C, with a response value of 20.5 (50ppm), response recovery time of 40s and 230s (50ppm), respectively, and has good selectivity, reproducibility (5 consecutive times), and long-term stability (70 days). The sensor has a good linear relationship between the concentration and response value of 0.5ppm to 50ppm 2-CEES gas. As the concentration of 2-CEES gas increases from 0.5ppm to 50ppm, the response of the sensor to 2-CEES gas also increases from 1.2 to 20.5.

[0113] Fig.15 These are the XRD image and SEM image of the NiO / Co3O4 gas-sensitive material in the ceramic tube with NiO / Co3O4 composite material grown on the surface prepared in step 4 of Example 6. As can be seen from the figure, the prepared material is a composite material of NiO and Co3O4, and the NiO / Co3O4 composite material grows tightly on the surface of the ceramic tube.

[0114] Fig.16 This is the response recovery curve of the gas sensor prepared in Example 6 to 50 ppm of 2-CEES gas at 150°C; it can be seen from the figure that the NiO / Co3O4 composite material sensor can detect 2-CEES gas.

[0115] The gas sensor prepared in Example 6 has the best gas-sensing performance at 150°C, with a response value of 6.3 (50ppm), response recovery time of 55s and 320s (50ppm), respectively, and has good selectivity, reproducibility (5 consecutive times), and long-term stability (70 days). The sensor has a good linear relationship between the concentration and response value of 2-CEES gas of 1ppm to 50ppm. As the concentration of 2-CEES gas increases from 1ppm to 50ppm, the response of the sensor to 2-CEES gas also increases from 1.2 to 6.3.

[0116] Fig.17 The XRD image and SEM image of the NiO / MgO gas-sensitive material in the ceramic tube with NiO / MgO composite material grown on the surface prepared in step 4 of Example 7; as can be seen from the figure, the prepared material is a composite material of NiO and MgO, and the NiO / MgO composite material grows tightly on the surface of the ceramic tube.

[0117] Fig.18This is the response recovery curve of the gas sensor prepared in Example 7 to 50 ppm of 2-CEES gas at 150° C. As can be seen from the figure, the NiO / MgO composite material sensor can detect 2-CEES gas.

[0118] The gas sensor prepared in Example 7 has the best gas-sensing performance at 150°C, with a response value of 21.5 (50ppm), response recovery time of 70s and 220s (50ppm), respectively, and has good selectivity, reproducibility (5 consecutive times), and long-term stability (70 days). The sensor has a good linear relationship between the concentration and response value of 0.5ppm to 50ppm 2-CEES gas. As the concentration of 2-CEES gas increases from 0.5ppm to 50ppm, the response of the sensor to 2-CEES gas also increases from 1.2 to 21.5.

Claims

1. A method for preparing a NiO-based 2-chloroethyl ethyl sulfide gas sensor, characterized in that It is carried out in the following steps:

1. Composite of nickel sulfate hexahydrate and metal salts: Dissolve nickel sulfate hexahydrate and metal salt in deionized water and stir magnetically to obtain a clear and transparent solution; 2. Add ammonia: Add ammonia water to the clear transparent solution and continue magnetic stirring to obtain a green solution; 3. Immersion Heating: The ceramic tube is immersed in the green solution and sealed, reacted for 4 hours to 24 hours at a temperature of 120°C to 200°C, then cooled to room temperature, the ceramic tube is taken out, washed and dried to obtain an immersed ceramic tube; 4. Calcination: The impregnated ceramic tube is calcined for 1 h to 4 h in an air atmosphere at a temperature of 400° C. to obtain a ceramic tube with a NiO / metal oxide composite material grown on the surface; The metal oxide is iron oxide, copper oxide, cadmium oxide, zinc oxide, silver oxide, cobalt oxide or magnesium oxide; 5. Aging: A ceramic tube with a NiO / metal oxide composite material grown on the surface is welded to a base and then subjected to an aging treatment to obtain a NiO-based 2-chloroethyl ethyl sulfide gas sensor.

2. The method for preparing a NiO-based 2-chloroethyl ethyl sulfide gas sensor according to claim 1, characterized in that The metal salt described in step 1 is ferric nitrate nonahydrate, copper acetate, cadmium acetate, zinc acetate, silver acetate, cobalt acetate or magnesium chloride.

3. The method for preparing the NiO-based 2-chloroethyl ethyl sulfide gas sensor according to claim 1, characterized in that The molar ratio of nickel sulfate hexahydrate to metal salt described in step 1 is 1:(0-0.2).

4. The method for preparing the NiO-based 2-chloroethyl ethyl sulfide gas sensor according to claim 1, characterized in that The volume ratio of the molar number of nickel sulfate hexahydrate described in step 1 to deionized water is 1 mmol: (5-20) mL.

5. The method for preparing the NiO-based 2-chloroethyl ethyl sulfide gas sensor according to claim 1, characterized in that The magnetic stirring described in step 1 is specifically for 0.5h to 2h at a rotation speed of 50rpm to 3000rpm; the magnetic stirring described in step 2 is specifically for 0.5h to 2h at a rotation speed of 50rpm to 3000rpm.

6. The method for preparing the NiO-based 2-chloroethyl ethyl sulfide gas sensor according to claim 1, characterized in that The volume ratio of the clear transparent solution described in step 2 to ammonia water is 1:(0.03-0.1).

7. The method for preparing a NiO-based 2-chloroethyl ethyl sulfide gas sensor according to claim 1, characterized in that The mass percentage of the ammonia water described in step 2 is 5% to 20%.

8. The method for preparing the NiO-based 2-chloroethyl ethyl sulfide gas sensor according to claim 1, characterized in that The ceramic tube described in step three is an Al2O3 ceramic tube.

9. The method for preparing a NiO-based 2-chloroethyl ethyl sulfide gas sensor according to claim 1, characterized in that In step 4, the temperature is increased to 400° C. to 700° C. at a heating rate of 1° C. / min to 5° C. / min under air atmosphere.

10. The method for preparing the NiO-based 2-chloroethyl ethyl sulfide gas sensor according to claim 1, characterized in that The aging treatment described in step 5 is specifically aging at a temperature of 90° C. to 150° C. for 24 h to 72 h.

Citation Information

Patent Citations

  • WO3 / Al2O3 / graphene composite material and preparation and application thereof

    CN116642928A

  • Ethanol gas sensor based on Al-doped NiO nano rod-flower material and preparation method thereof

    CN104990961A

  • NiO oxide semiconductor xylene sensor and preparation method and application thereof

    CN110082398A

  • Preparation method and application of NiO-SnO2 composite material with flower-like structure

    CN112320859A

  • Quartz crystal microbalance sensor and detection method for mustard gas and mustard gas simulant by using sensor

    CN114019019A